Implementation of Village Budget and Expenditure Budget (APBDes) in 2019 Suka Ramai Village, Padang Tualang District, Langkat Regency, Indonesia - Jalilah Ilmiha; Lusi Elviani Rangkuti; Farida Khairani Lubis; Shofwan Andri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the implementation of the Village Revenue and Expenditure Budget (APBDes) in Suka Ramai Village, Padang Tualang District, Langkat Regency, Indonesia. This research is motivated by the fact that several areas are still found related to irregularities in village financial management. Data collection techniques used in this study were interviews, observation. The data analysis method in this study used a descriptive analysis method with a qualitative approach. The resource persons in this study were the village head, village secretary, and village treasurer in Suka Ramai Village. The results of this study indicate that the APBDes program in Suka Ramai Village has implemented the concept of participatory development of rural communities as evidenced by the application of participatory principles. And the implementation of the APBDes program in Suka Ramai Village has implemented transparent, accountable, participatory principles in accordance with the Minister of Home Affairs Regulation (Permendagri) No. 113 of 2014.